Efficient photoreduction of carbon dioxide with modified g-C3N4 photocatalyst - Pek, Jing Yang, (2017)
As a well known conjugated polymer, graphitic carbon nitride (g-C3N4) has made head news in research field as and attracted broad interdisplinary attention as a metal-free and sunlight responsive photocatalyst to be used in applications such as solar energy conversion, environmental remediation and even capacitor storage devices. This is due to its suitable electronic band structure, high chemical and thermal stability. This review showcases, the various approaches to sythesize heterostructure nanocomposites with g-C3N4 used either as bulk or dopant, in conjunction with a metal, metal-oxide or noble metal co-catalyst nanoparticles loading. As such attempt to enhance charge separation and thereby improving photocatalysis efficiency by Mott-Schottky heterojunction mechanism. Furthermore, we will also discuss the photovoltaic mechanisms on how photoelectron-hole pairs transport acoss g-C3N4, and how the charges participate in redox reactions to produce renewable energy and clean by-products. Aside from that, our experiment aims to validate the capability of g-C3N4 in photoreduction of CO2 with the aid of Pyrene coating as well as pyrene coating’s role in aiding photohole transport across g-C3N4 substrate. Lastly, this comprehensive review compels to explore improvements to current g-C3N4 photocatalyst methods and open more avenues for its applications with better performances towards the development of a green and sustainable future.